2020
DOI: 10.51381/adrs.v3i2.34
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Covid-19 Crisis Management in Cameroon: Decentralised Governance Response Needed

Abstract: This article provides insights into Cameroon’s crisis management of the coronavirus pandemic via an exploratory and descriptive qualitative research. Thematic analysis of data was done using a framework approach; the Comprehensive Pandemic Risk Management System (CPRMS) underpins the research and provided structure, order, and clarity to the article. From the findings, one can deduce that the government is working hard to mitigate the potentially awful consequences of the coronavirus pandemic. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(28 reference statements)
0
2
0
1
Order By: Relevance
“…The provision of regular clean portable drinking water to many local communities and well-equipped health centers and clinics would be helpful to curb these health risks. For instance, COVID-19 exposed the fragile state of Cameroon's health system and the country's low resilience to the pandemic [18] with related governance issues in the management of the crisis [119]. Being proactive in sustaining the health care system is critical in tackling these hazards including unprecedented pandemics like COVID-19.…”
Section: Biological and Health Hazardsmentioning
confidence: 99%
“…The provision of regular clean portable drinking water to many local communities and well-equipped health centers and clinics would be helpful to curb these health risks. For instance, COVID-19 exposed the fragile state of Cameroon's health system and the country's low resilience to the pandemic [18] with related governance issues in the management of the crisis [119]. Being proactive in sustaining the health care system is critical in tackling these hazards including unprecedented pandemics like COVID-19.…”
Section: Biological and Health Hazardsmentioning
confidence: 99%
“…Another study conducted in 2020 revealed a high score of knowledge among Cameroonians, but the attitudes and practice scores were lower [15]. From this limited literature, researchers have highlighted a need for additional education surrounding COVID-19, particularly on modes of transmission, control, and prevention [16,17]. However, exploring how COVID-19 is perceived and experienced by members of the community in Cameroon can better explain the relationship between knowledge and, attitudes and practice.…”
Section: Introductionmentioning
confidence: 99%
“…serait décentralisée vers les régions et les échelons locaux(Bang 2020). En fonction de leurs capacités techniques, les écoles et les enseignants ont été encouragés à mettre en oeuvre des solutions parallèles aux programmes de télévision éducative mandatés par le gouvernement central, ce qui a conduit à la prolifération de discussions de groupe WhatsApp, de comptes Google classroom et d'applications de tutorat en ligne (Beche 2020).…”
unclassified